Association between diabetes mellitus and angina after acute myocardial infarction: analysis of the TRIUMPH prospective cohort study. (29th August 2020) - Arnold, Suzanne V; Spertus, John A; Lipska, Kasia J; Tang, Fengming; Goyal, Abhinav; McGuire, Darren K; Cresci, Sharon; Maddox, Thomas M; Kosiborod, Mikhail
Abstract: Aims: While patients with diabetes mellitus (DM) have more extensive coronary disease and worse survival after acute myocardial infarction (AMI) than patients without DM, data on whether they experience more angina are conflicting. Methods: We examined angina prevalence over the year following AMI among 3367 patients, including 1080 (32%) with DM, from 24 US hospitals enrolled in the TRIUMPH registry from 2005 to 2008. Results: Patients with vs. without DM were more likely to be treated with antianginal medications both at discharge and over follow up. Despite more aggressive angina therapy, patients with vs. without DM had higher prevalence and severity of angina prior to AMI (49 vs. 43%, p  = 0.001) and at each follow-up assessment, although rates of angina declined in both groups over time. In a hierarchical, multivariable, repeated-measures model that adjusted for multiple demographic and clinical factors including severity of coronary disease and in-hospital revascularization, DM was associated with a greater odds of angina over the 12 months of follow up; this association increased in magnitude over time (12-month OR 1.18, 95% CI 1.01–1.37; DM*time p interaction  = 0.008). Conclusions: Contrary to conventional wisdom, angina is more prevalent and more severe among patients with DM, both prior to and following AMI. This effect is amplified over time and independent of patient and treatment factors, including the presence of multivessel disease and coronary revascularization. This increased burden of angina may be due to more diffuse nature of coronary disease, more rapid progression of coronary disease over time, or greater myocardial demand among DM patients.